Translation and validation of the Treatment Motivation Questionnaire (TMQ) to Malay Version - Amelia Mohd Noor (Tanjong Malim, 2021)
Translation and validation of the Treatment Motivation Questionnaire (TMQ) to Malay Version by Amelia Mohd Noor